Exercise to Lower Postprandial Lipemia: Why, When, What and How - Petridou, Anatoli; Mougios, Vassilis (International Journal of Sports Medicine, 2022)
We review recent findings on the ability of exercise to lower postprandial lipemia (PPL). Specifically, we answer why exercise is important in lowering PPL, when it is most effective to exercise to achieve this, what the preferred exercise is and how exercise reduces PPL. Most findings confirm the power of exercise to lower PPL, which is an independent risk factor for cardiovascular disease. Exercise is most effective when performed on the day preceding a high- or moderate-fat meal. This effect lasts up to approximately two days; therefore, one should exercise frequently to maintain this benefit. However, the time of exercise relative to a meal is not that important in real-life conditions, since one consumes several meals during the day; thus, an exercise bout will inevitably exert its lowering effect on PPL in one or more of the subsequent meals. Although moderate-intensity continuous exercise, high-intensity intermittent exercise, resistance exercise and accumulation of short bouts of exercise throughout the day are all effective in lowering PPL, submaximal, high-volume interval exercise seems to be superior, provided it is tolerable. Finally, exercise reduces PPL by both lowering the rate of appearance and increasing the clearance of triacylglycerol-rich lipoproteins from the circulation.
Keywords: cardiovascular disease; meal; physical activity; triacylglycerol